Uso da tampa interna da colmeia Langstroth na manutenção da homeostase em colônias de abelhas africanizadas Apis mellifera durante o período de estiagem no semiárido nordestino - Fernandes, Nayanny de Sousa (2013)
The Langstroth hive has its original model in an inner lid, just below the lid which would serve to assist the bees in the nest thermoregulation. In Brazil, the inner cover was removed from the hive components on the grounds that the country is tropical and the inner cover would become unnecessary, but no study has been done in this direction. The present study aims to investigate the role of the inner cover of the hive Langstroth homeostasis of Africanized bee colonies Apis mellifera in the dry season in the Caatinga in Limoeiro Norte-Ceará. The survey was conducted in October and November 2012 at the site of Canafístula Bixopá, District Bixopá, in the city of Limoeiro do Norte, state of Ceará. The experiment consisted of 10 hives without inner cover (T1) and 10 hives with inner cover (T2), in which he recorded temperature and relative humidity in the hives, ventilation (intensity and number of workers fanning), water harvesting (number of collecting bees by time, number of trips per bee, interval between the journeys and time spent for collection), and the consumption of food reserves from the hives of the two treatments. The results showed a significant difference (p <0.05) for temperature and relative humidity in the hives, with averages differing significantly between T1 (32.08 ± 0,27ºC and 53.23 ± 0.62%) and T2 (31.60 ± 0,33ºC and 54.96 ± 0.75%). The intensity data of ventilation, and the number of fanning bees did not differ between T1 (20.65 ± 0.77mm and 0.62 ± 0.14 bees) and T2 (20.27 ± 0.86mm and treatments 0.3 ± 0.06 bees). In collecting water, there was no statistical difference in the times of 11:00, 15:00 and 16:00 in T1 (16.25 ± 2.05, 18.25 ± 2.28 and 14.00 ± 1.35 treatments) and T2 (8.25 ± 1.88, 12.25 ± 0.62 and 9.75 ± 0.75), as well as the time spent collecting water (T1 = 34.86 ± 0.56s and T2 = 37.64 ± 0.63s). The number of trips / bee / day differed between the T1 and T2 only between quartiles I and II (Q1T1: 11.25 ± 4.52; Q2 T1: 35.5 ± 22.22; Q1T2: 4 ± 1.71, Q2 T2: 25.5 ± 15.28), for the Man-Whitney test. In between trips was no statistical difference only in quartiles I, II and IV of T1 treatments (Q1T1: 6 ± 5.13; Q2 T1: 8 ± 7.41 and Q4 T1: 97 ± 23.50 min) and T2 (Q1T2: 5.25 ± 3.94; Q2 T2: 8 ± 6.94 and Q4 T2: 272 ± 82.29 min) for the Man-Whitney test. The average consumption of food supply did not differ between treatments, being in T1 177.7 ± 29.9g and 141.8± 3.8g in T2. We conclude that the inner cover of the hive Langstroth provides that these bees hives achieve better conditions of internal homeostasis of the nest giving off less effort than those of hives without inner cover in conditions of the Limoeiro do Norte, Ceará.